Influência de materiais de proteção na resistividade elétrica do concreto - Santor, M. S.; Gastaldini, A. L. G.; Crauss, C.; dos Santos, G. T.; Rossini, F. C. (Revista ALCONPAT, 2012)
The durability of concrete structures is a result of the protective action of concrete on the reinforcement. When there is no passivation of steel, the structure becomes vulnerable to corrosion, and once corrosion starts its propagation is essentially controlled by the electrical resistivity of concrete. The objective of this study was to evaluate the change in electrical resistivity of concretes produced with different types of cement: CP II F, CP IV and CP V that were surface-treated with pore filler and polymer mortar. For analysis purposes, the results were compared with those of the blanks that were not subjected to surface treatment.These treatments were performed in concretes with the following compressive strengths at the age of 28 days: 21.6 MPa, 26.6 MPa and 31.6 MPa. For all types of cement used and strengths adopted, surface treatment with polymer mortar led to higher electrical resistivity values.Key words: concrete; durability; surface protection material; electrical resistivity